Web caching and content switching for performance of content delivery - Dimitrievski, Ace; Trajkovikj, Vladimir; Filiposka, Sonja (IEEE, 2015)
With the emergence of web 2.0 the web has evolved from informational posting board to rich application platform. Web applications have replaced desktop applications from office productivity to 3d rendering. In this paper we'll present issues that degrade user web experience and increase demand for resource as well as techniques for mitigating those issues. We'll specially focus on large legacy web sites with legacy infrastructure. The example that we will work on is the main site of a large international organization.
Keywords: Content delivery network (CDN), Content switching, Load balancing, Web